Heaven, Hell and Middangeard: The Presentation of the Universe in the Old English Genesis A - Olesiejko, Jacek (Studia Anglica Posnaniensia, 2009)
Since the times of Antiquity, people have looked up to the sky and developed various conceptions of Heaven and Hell. Already in the ancient Egypt people developed the tripartite conception of universe with earth placed between the Heaven inhabited by gods above and Hell below. The Old English poetic text of Genesis (MS Junius 11; compilation dated to the 10th century) presents the earthly paradise, Hell and Middangeard (or the middle earth). Both Genesis A and B that comprise the poem indeed show a single and consistent descriptions of cosmos. The overt consistency may well seem as interesting as the tradition that the poem draws upon as well as distorts. The universe found in the poem is a fusion of the Christian religious learning as well as Germanic tradition. The idea that marries Heaven, earth and Hell in the poetic sequence of OE Genesis is the concept of hall and anti-hall, city and anti-city. The aim of the following paper is to investigate the modes of this presentation of these parts of the universe by the analysis of the clusters of meaning that are associated with hall and city.